2006
DOI: 10.1038/sj.npp.1301191
|View full text |Cite
|
Sign up to set email alerts
|

The Ampakine CX546 Restores the Prepulse Inhibition and Latent Inhibition Deficits in mGluR5-Deficient Mice

Abstract: In order to test the possible role of mGluR5 signaling in the behavioral endophenotypes of schizophrenia and other psychiatric disorders, we used genetic engineering to create mice carrying null mutations in this gene. Compared to their mGluR5 + / + littermates, mGluR5 À/À mice have disrupted latent inhibition (LI) as measured in a thirst-motivated conditioned emotional response procedure. Administration of the positive modulator of a-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid receptors (AMPAR), CX546… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 72 publications
5
26
0
Order By: Relevance
“…Following enrichment, the response to MK-801 in mGlu5 KO mice was potentiated, with KO mice showing significantly higher levels of hyperactivity compared with KO mice housed in standard conditions. In agreement with the previous finding, the current work demonstrated impaired PPI in mGlu5 KO mice to a level that was not disrupted further by MK-801 (Lipina et al, 2007). This is unlikely to be a 'floor' effect caused by reduced baseline levels of PPI in mGlu5 KO mice, as it has been shown that higher doses of MK-801 than those used in the present study can elicit further disruptions in PPI in mGlu5 KO mice compared with saline controls, suggesting that KO mice show a reduced sensitivity to the drug rather than a complete resistance (Lipina et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Following enrichment, the response to MK-801 in mGlu5 KO mice was potentiated, with KO mice showing significantly higher levels of hyperactivity compared with KO mice housed in standard conditions. In agreement with the previous finding, the current work demonstrated impaired PPI in mGlu5 KO mice to a level that was not disrupted further by MK-801 (Lipina et al, 2007). This is unlikely to be a 'floor' effect caused by reduced baseline levels of PPI in mGlu5 KO mice, as it has been shown that higher doses of MK-801 than those used in the present study can elicit further disruptions in PPI in mGlu5 KO mice compared with saline controls, suggesting that KO mice show a reduced sensitivity to the drug rather than a complete resistance (Lipina et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
“…In agreement with the previous finding, the current work demonstrated impaired PPI in mGlu5 KO mice to a level that was not disrupted further by MK-801 (Lipina et al, 2007). This is unlikely to be a 'floor' effect caused by reduced baseline levels of PPI in mGlu5 KO mice, as it has been shown that higher doses of MK-801 than those used in the present study can elicit further disruptions in PPI in mGlu5 KO mice compared with saline controls, suggesting that KO mice show a reduced sensitivity to the drug rather than a complete resistance (Lipina et al, 2007). Thus, the present results cannot be explained simply by altered baseline PPI in standard-housed or environmentally-enriched KO mice.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations